Socio-Economic Constraints In Livestock Rearing For Self Help Group Members And Non-Members - Varathan, B. Jaya; Prabu, M.; Pandian, A. Serma Saravana; Kumar , G. Senthil (Indian Journal of Veterinary Sciences and Biotechnology, 2011)
A study was carried out in Tiruvannamalai district of Tamil Nadu to evaluate the social, economic and political constraints in livestock rearing as perceived by women SHG members and non members. A detailed questionnaire among various aspects of socio-economic and political constraints involved in livestock rearing were enlisted and women livestock farmers from SHG members and non-members in the study area were asked to rank each constraint which was then analyzed using Garret’s ranking technique. The results showed that SHG member’s perceived lack of gender based academic institutions causing illiteracy and lack of agro based industries in rural atmosphere as their vital constraints whereas non-members perceived these constraints trivially. Both SHG members and non-members identified unhealthy traditions and customs existing in the social atmosphere insignificantly.